ÁMIWDÁRYA DELTASÍ ÚY TÍShQANLARÍ MUS MUSCULUS NEMATODA KLASÍ GELMINTLERI - Berdibaev, Abat Sultamuratovich (SCIENCE and SOCIETY, 2026)
As a result of helminthological studies, it was found that out of 61 domestic mice, 27 individuals were infected with nematode class helminths by 44.3%. 9 species of nematodes belonging to 1 type, 1 class, 4 orders, 6 families were registered. The helminths identified in mice according to their development cycle are classified as 7 species of hyogelmins, and 2 species as biohelminths.